COUNTER LEGAL DRAFT KOMPILASI HUKUM ISLAM - Efizal A (Institut Darul Quran Payakumbuh, 2017)
The presence of Islamic Law Compilation is one of the referent forms in solving any cases in Religious Justice, which is to solve deviation of justice decision which is driven by extreme different ideas. Islamic Law Compilation is a combination of applied law regulation which is applied at Religious Justice based on President Instruction number 1, 1991 in Indonesia. However, in accordance with the development of civilization, a team of Ministry of Religious Affairs, in the name of gender equivalence, considers that the old Islamic Law Compilation is not suitable to the current time. Therefore, it needs to renew the Islamic Law Compilation because there are many discriminative chapters to women in it. Thus, the team of gender equivalence wants to increase the degree of women and formulate a draft based on the principles of democracy, justice, gender equivalence, and pluralism. Anyhow, after studying and conducting research, the Counter Legal Draft of Islamic Law Compilation, discovered by Siti Musda Mulia, Cs., is contradictive to Islamic teaching (al-Quran and Hadith). According to them, the draft of Counter Legal Draft of Islamic Law Compilation is a renewing of Islamic law. After reading several norms formulated by them, the writer thinks that is not a renewing Islamic law, but a misleading formulation that is far from the real Islamic law. Also, the renewing shows a liberal reformation that does not deal with Islamic law (Al-Qur’an and Hadist), but it is based on Western principles that idols democratic and structure values.